2018
DOI: 10.1021/acs.macromol.8b02088
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Amplified Stereoselectivity (PASS) of Asymmetric Michael Addition Reaction and Aldol Reaction Catalyzed by Helical Poly(phenyl isocyanide) Bearing Secondary Amine Pendants

Abstract: A novel enantiopure phenyl isocyanide (1) carrying tert-butyloxycarboryl (Boc) protected L-prolinol ester was designed and synthesized. Living polymerization of 1 using a alkyne−Pd(II) catalyst afforded helical poly-1 m s in high yields with controlled molecular weights (M n s) and narrow molecular weight distributions (M w /M n s). Removing the protecting Boc groups on the L-prolinol ester pendants lead to the formation of helical poly-2 m , which showed high optical activity owing to the preferred left-hande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
(50 reference statements)
0
30
0
Order By: Relevance
“…The application of optically active helical polymers for asymmetric catalysis has also attracted growing interest, because a one‐handed helical chirality can significantly contribute to the enantioselectivity due to a one‐handed helical arrangement of the catalytically active, chiral/achiral units along the one‐handed helical polymer backbone . Up to now, a variety of helical polymer‐based asymmetric catalysts have been developed mainly by introducing catalytically active, chiral/achiral units as components in or along artificial helical polymers that involve polyacetylenes, poly(methacrylate)s, polyisocyanates, polyisocyanides, and poly(quinoxaline‐2,3‐diyl)s . In these cases, the use of optically active monomers is essential to control their helical handedness except for poly(methacrylate)s with a bulky pendant prepared by helix‐sense‐selective polymerization using chiral catalysts or initiators .…”
Section: Introductionmentioning
confidence: 99%
“…The application of optically active helical polymers for asymmetric catalysis has also attracted growing interest, because a one‐handed helical chirality can significantly contribute to the enantioselectivity due to a one‐handed helical arrangement of the catalytically active, chiral/achiral units along the one‐handed helical polymer backbone . Up to now, a variety of helical polymer‐based asymmetric catalysts have been developed mainly by introducing catalytically active, chiral/achiral units as components in or along artificial helical polymers that involve polyacetylenes, poly(methacrylate)s, polyisocyanates, polyisocyanides, and poly(quinoxaline‐2,3‐diyl)s . In these cases, the use of optically active monomers is essential to control their helical handedness except for poly(methacrylate)s with a bulky pendant prepared by helix‐sense‐selective polymerization using chiral catalysts or initiators .…”
Section: Introductionmentioning
confidence: 99%
“…The higher CD value for PPI 50 (CD = 21) compared to that of PPI 20 (CD = 18) suggests a relatively stable and stereoregular helix conformation caused by the relatively long chain length of PPI 50 . [ 38 ] Importantly, their corresponding copolymers of EC‐2,3‐g‐PPI 20 and EC‐2,3‐g‐PPI 50 also showed a dramatically enhanced Cotton effect at the same wavelength, with a CD value increase of 146% and 302% compared to those of PPI 20 and PPI 50 , respectively. The CD value also increased by the grafting degree of PPI 50 on EC‐2,3‐g‐PPI 50 , which is apparent in Figure 6C.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al reported the synthesis of helical poly(phenyl isocyanide) bearing L-prolinol derivative as pendant by living polymerization with controlled molecular weights and narrow molecular weight distributions. 36 The helical polymeric catalysts were applied to an asymmetric Michael addition and an aldol reaction. The catalytic activity was linearly correlated with the molecular weight (M n ) and optical activity of the polymeric catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The polymeric catalyst could be successfully reused several times with little change in yield and only small losses in selectivity. Wu et al reported the synthesis of helical poly(phenyl isocyanide) bearing l ‐prolinol derivative as pendant by living polymerization with controlled molecular weights and narrow molecular weight distributions 36 …”
Section: Introductionmentioning
confidence: 99%